PERGESERAN DAN PEMERTAHANAN BAHASA KERINCI DIALEK SIULAK DI KECAMATAN SIULAK MUKAI KABUPATEN KERINCI - Karmizi, Yoga; Syofiani, Syofiani; Morelent, Yetty (Universitas Batanghari, 2024)
The aim of research on the shift and maintenance of the Siulak dialect of the Kerinci language in Siulak Mukai District, Kerinci Regency, is to describe the form of shift and maintenance of the Siulak dialect of the Kerinci language. This research is motivated by the frequent use of Indonesian and other regional languages in greetings. The type of research used is qualitative research with descriptive methods. The data source is speech expressed by the people of Siulak Mukai subdistrict. Data acquisition techniques were carried out using observation and interview techniques. The data analysis technique consists of two activities that take place simultaneously, namely data reduction and data presentation. The results of the research show that there has been a shift in the Kerinci language to the Siulak dialect in Siulak Mukai District due to social factors and current developments.